ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DINAS KETAHANAN PANGAN KABUPATEN LAMANDAU - Sofia Anitawati (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
Performance is a very important factor in an organization, because it can be used as a reference or benchmark to measure the level of success of the business organization in a certain period. The aim of this research is to determine the influence of leadership, motivation and work environment on employee performance at the Lamandau Regency Food Security Service. This type of research is associative quantitative. Researchers used saturated sampling. The sample from this research consisted of 31 respondents. The data obtained in this research was obtained directly from filling out the questionnaire. The analytical method used is the multiple linear regression equation. The research results obtained by testing the t hypothesis on the leadership variable were significant at 0.287 > a = 0.05 and t test = 1.085 < t table = 2.052, thus H1 was rejected, meaning that leadership had no significant effect. The motivation variable has a significance of 0.000 < a = 0.05 and t test = 4.664 > t table = 2.052, thus H2 is accepted, meaning that motivation has a significant effect. The work environment variable has a significance of 0.001 > a = 0.05 and t test = 3.820 > t table = 2.052, thus H3 is accepted, meaning the work environment has a significant effect. The results of the F hypothesis test show a significance of 0.000 < a = 0.05 and the calculated F value is 57.421 > F table of 2.048, thus H4 is accepted, meaning that leadership, motivation and the work environment simultaneously influence performance.